ANALISIS IMPLEMENTASI ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) SEBAGAI BENTUK PENERAPAN EKO-EFISIENSI DALAM MEWUJUDKAN KINERJA EKONOMI PERUSAHAAN - Nadya Talitha; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2022)
This research is a case study with an interpretive paradigm. It aims to describe the role of the EMA system in achieving eco-efficiency in a Company and its impact on the Company's economic performance. This study took up a manufacturing company in Semarang, Indonesia, as an object of observation.The results indicated that the Company has carried out environmental management activities, especially waste management, well, but reports on environmental costs are still standard based on government regulations and combine costs related to the environment into one account. This study identified environmental costs into four categories: environmental prevention costs, environmental detection costs, environmental internal failure costs, and environmental external failure costs. By separating environmental costs into each category in applying the Environmental Management Accounting (EMA) system, companies can obtain information for decision making and controlling environmental costs to achieve eco-efficiency. In the last years, the Company's profit has increased, reflecting the Company's economic performance after implementing the EMA system.